Essays on life sciences : with related science fiction stories - Luisi, P. L. (Cambridge Scholars Publishing, 2020)
This collection of essays highlights, in a new, critical fashion, some of the classic questions in life science. These include ""what is life?""; ""what is death?""; ""what is consciousness?""; ""why is life cellular?""; and ""why are enzymes macromolecules?"". It also explores whether evolution is pre-determined, whether science and spirituality can harmonize with each other, whether artificial intelligence is at odds with the human spirit, and whether, and to what extent, we are genetically determined. In this text, some of the main conceptual tools used to tackle life's many aspects are nec.